4.8k views
4 votes
Solve for x: −2(4 − 2x) + 3x = 2x + 2(5 + x) − 6

User SstrykerR
by
5.3k points

2 Answers

5 votes

Answer:

x=4

Explanation:

−2(4 − 2x) + 3x = 2x + 2(5 + x) − 6 (DISTRUBUTE)

-8+4x+3x=2x+10+2x-6 (SIMPLFY)

-8+7x=4x+4 (SUBTRACTE 4X FROM BOTH SIDES)

3x-8=4 (ADDD 8 TO BOTH SIDES)

3x=12 (DIVIDE MY 3 ON BOTH SIDES)

x=4

User Abigwonderful
by
6.3k points
1 vote

Answer:


\displaystyle 4 = x

Explanation:

−2(4 − 2x) + 3x = 2x + 2(5 + x) − 6

8 + 4x + 3x = 2x + 10 + 2x − 6

−8 + 7x = 4 + 4x

- 4 - 7x - 4 - 7x

________________


\displaystyle (-12)/(-3) = (-3x)/(-3) \\ \\ 4 = x

I am joyous to assist you anytime.

User Lamin
by
6.2k points